Explaining the success of Tunisia's democratic transition. (c2016) - Nader, Noura Raghdan (2016)
This thesis investigates the democratic transition in Tunisia and the reasons behind its success. It starts by examining the nature of democracy and the different factors that affect democratic transitions. The role of political economy, social cleavages and struggle, institutions, religion, and political agents in democratic transitions is contrasted among Arab states and thoroughly examined in Tunisia’s case. This study showed how the circumstances became favorable for the Tunisian Uprising to occur in 2011 by presenting the history of Tunisia including the evolution of the Tunisian General Labor Union (UGTT) and the economic liberalization the country had undergone, in addition to highlighting the role of social media. Moreover, Tunisia was the only country among the Arab Spring countries that experienced authoritarian breakdown and was also able to embark on a successful democratic transition. The process of this democratic transition is comprehensively explored by analyzing the role of the military, interim government, electoral politics, and the drafting of the new constitution. Tunisia's political actors and elites were committed to protect their new democratic principles, the constitution-making process was very inclusive and transparent, and the electoral reforms that were adopted gave a chance for other political parties to participate and compete in elections. The Arab spring was born in Tunisia and finally resulted in a successful democratic transition in the country.